2004
DOI: 10.1182/blood-2003-01-0069
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of human parvovirus B19 in children with sickle cell disease

Abstract: Human parvovirus (HPV) B19 causes significant morbidity and mortality in children with sickle cell disease (SCD), but little data are published about the epidemiology of HPV B19 infection and its associated complications in this patient population. In this study, prevalence and incidence rates of HPV B19 were determined in 633 patients with SCD followed at The Children's Hospital of Philadelphia between November 1996 and December 2001. Thirty percent (30%) were HPV B19 immunoglobulin G (IgG) positive at first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
4
13

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 26 publications
(31 reference statements)
12
81
4
13
Order By: Relevance
“…Parvovirus B19 frequently causes transient red cell aplasia (TRCA) in children with sickle cell disease [30]. Other parvovirus B19-related complications include acute splenic sequestration, hepatic sequestration, acute chest syndrome, nephrotic syndrome, meningoencephalitis, and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Parvovirus B19 frequently causes transient red cell aplasia (TRCA) in children with sickle cell disease [30]. Other parvovirus B19-related complications include acute splenic sequestration, hepatic sequestration, acute chest syndrome, nephrotic syndrome, meningoencephalitis, and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In a single institution observational study of Parvovirus B19 -induced RBC aplasia, the median nadir hemoglobin was 4.8 gm/dL and 49 of 68 pediatric patients (72%) received a simple RBC transfusion. 31 Because the anemia associated with RBC aplasia is subacute, the patient is typically euvolemic and physiologically compensated. Therefore, RBC transfusion should be administered slowly with serial small aliquots to prevent congestive heart failure.…”
Section: Acute Exacerbation Of Anemiamentioning
confidence: 99%
“…Smith-Whitley et al [19] reported that 18% and 27% of SCD patients with parvovirus-related aplastic crisis had neutropenia or thrombocytopenia, respectively. We found, in contrast, that 65% of patients with HS or thalassemia had leukopenia or neutropenia and 71% had thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%